Relationship between the level of blood plasma amino acids with daily amount of group ventricular extrasystoles and the duration of pain or painless myocardial ischemia in patients with stable and unstable angina - Bogdan, T.V. (Доповіді НАН України, 2020)
It is now known that the human body suffering from coronary heart disease is trying to adapt to new working conditions through biochemical rearrangements, one of which is to increase the involvement of amino acids in car diomyocyte metabolism. Amino acids are metabolized in the myocardium under normal conditions, myocardial ischemia leads to a major restructuring of biochemical reactions, which increases the use of amino acids as metabolites. It is proved that myocardial ischemia, painless myocardial ischemia, and group ventricular extrasystoles are prognostic indicators of the adverse course of ischemic heart disease. According to the results of the study, in patients with stable (SA) or unstable angina (UA), the reliable correlations between the frequency of group ventricular extrasystoles and painless or painful myocardial ischemia with the levels of arginine, the amount of sulfur-containing amino acids and amino acids with branched lateral chain are formed. This indicates the pathogenetic role of the imbalance of the amino acid spectrum of blood plasma in the development of atherosclerosis, destabilization of coronary circulation, and the emergence of cardiac arrhythmia. Відомо, що організм людини, яка страждає на ішемічну хворобу серця, намагається пристосуватися до нових умов життєдіяльності шляхом біохімічних перебудов, одна з яких – залучення більшої кількості амінокислот до метаболізму кардіоміоцитів. Амінокислоти метаболізуються в міокарді і за нормальних умов, міокардіальна ішемія призводить до значної перебудови біохімічних реакцій, внаслідок якої посилюється використання амінокислот як метаболітів. Доведено, що больова ішемія міокарда, безбольова ішемія міокарда та групова шлуночкова екстрасистолія є прогностичними показниками несприятливого перебігу ішемічної хвороби серця. За результатами дослідження, у хворих на стабільну або нестабільну стенокардію формуються достовірні кореляційні зв'язки між частотою групових шлуночкових екстрасистол, безбольової і больової ішемії міокарда з рівнем аргініну, суми сірковмісних амінокислот та амінокислот з розгалуженим бічним ланцюгом у плазмі крові. Це свідчить про патогенетичну роль дисбалансу амінокислотного спектра плазми крові в розвитку атеросклерозу, дестабілізації коронарного кровообігу та виникненні порушень серцевого ритму.